Yellow fever transmission in non-human primates, Bahia, Northeastern Brazil. - Jaqueline Goes de Jesus; Tiago Gräf; Marta Giovanetti; Maria Angélica Mares-Guia; Joilson Xavier; Maricelia Lima Maia; Vagner Fonseca; Allison Fabri; Roberto Fonseca Dos Santos; Felicidade Mota Pereira; Leandro Ferraz Oliveira Santos; Luciana Reboredo de Oliveira da Silva; et al. (Public Library of Science (PLoS), 2020)
Yellow fever virus (YFV) causes a clinical syndrome of acute hemorrhagic hepatitis. YFV transmission involves non-human primates (NHP), mosquitoes and humans. By late 2016, Brazil experienced the largest YFV outbreak of the last 100 years, with 2050 human confirmed cases, with 681 cases ending in death and 764 confirmed epizootic cases in NHP. Among affected areas, Bahia state in Northeastern was the only region with no autochthonous human cases. By using next generation sequence approach, we investigated the molecular epidemiology of YFV in NHP in Bahia and discuss what factors might have prevented human cases. We investigated 47 YFV positive tissue samples from NHP cases to generate 8 novel YFV genomes. ML phylogenetic tree reconstructions and automated subtyping tools placed the newly generated genomes within the South American genotype I (SA I). Our analysis revealed that the YFV genomes from Bahia formed two distinct well-supported phylogenetic clusters that emerged most likely of an introduction from Minas Gerais and Espírito Santo states. Vegetation coverage analysis performed shows predominantly low to medium vegetation coverage in Bahia state. Together, our findings support the hypothesis of two independent YFV SA-I introductions. We also highlighted the effectiveness of the actions taken by epidemiological surveillance team of the state to prevented human cases.